EFEKTIVITAS PENDEKATAN SAINTIFIK PADA TEMA 6 TERHADAP HASIL BELAJAR SISWA KELAS III SD - Alfita Kuni (Program Studi PGSD STKIP PGRI Banjarmasin, 2020)
The purpose of this study was to determine the effectiveness of the application scientific approach to student learning outcomes on the theme 6 of the beauty of class III Elementary School. This research is a pre-experimental study with the research design of the One Group Pretest Posttest. The population in the study were third grade Elementary School students. The research sample was class III students. Data collection techniques using the test method. Learning outcomes before and after the use of the scientific approach can be known to use te test. The test used in the form of multiple choice questions. Data in the study were analyzed using analysis with the help of SPSS 16.00 for windows. Testing the hypothesis to find out the effectivenness of the use scientific approach in the study was conducted by comparing the average learning outcomes before and after being treated. The results of this study indicate that the average value of student learning outcomes after being given better treatment, namely 84,21>53,42. This study can be concluded that the use of a scientific approach is effective on student learning outcomes.